From ADHD Diagnosis to Meaning: Does Grief Theory Enhance Our Understanding of Narrative Reconstruction? - Lynam, Aoife; Mc Guckin, Conor (My University, 2025)
While having or raising a child with a neurodivergence can be rewarding and life-enhancing, a diagnosis may trigger stress as people adapt to and navigate a new “assumptive world”. The purpose of this paper is to draw on the Attention Deficit Hyperactivity Disorder (ADHD) literature and explore it using grief theory as a conceptual framework, so as to understand parents’ and adults’ potential reactions to a diagnosis of ADHD. A narrative review of the ADHD literature suggests that adapting to a diagnosis can be understood as a process, which can occur in decisions to seek, and in reactions to, a diagnosis. For some, diagnostic work can be abrupt and unexpected, a life-changing moment when one receives an initial diagnosis. For others, diagnostic work begins pre-diagnosis. Either way, the diagnostic process requires an adjustment. This adaptation, like grief, can be ongoing and can involve a psychosocial transition. Rather than traditional models of grief (e.g., Freud and Kübler-Ross), contemporary views of grief such as the Dual Process Model and Meaning Making enable us to understand the meaning-making that is central to diagnostics work. Pre-diagnostically, people must become aware that something is different than previous expectations, in order to seek a diagnosis. Exposure to ADHD knowledge and stigma is influential pre-diagnostically. Post-diagnostically, people encounter a range of emotions which they need to process, such as grief for the past, making decisions (e.g., treatment), worries for the future, and reconstructing identity. The neurodiversity paradigm poses opportunities and challenges for people within this meaning-making process. This paper identifies implications for practice, particularly around pre- and post-diagnostic support, and directions for future research.
PUBLISHED
Keywords: grief; loss; diagnosis; disability; neurodiversity; parents; adults; adjustment; psychosocial adaptation